Demonstration of GaN/LiNbO3 Hybrid Wafer Using Room-Temperature Surface Activated Bonding. (23rd April 2020) - Takigawa, Ryo; Matsumae, Takashi; Yamamoto, Michitaka; Higurashi, Eiji; Asano, Tanemasa; Kanaya, Haruichi
Abstract : In this study, a GaN/LiNbO3 hybrid wafer was demonstrated using room-temperature bonding based on a surface activated bonding (SAB) method. The SAB using Fe-containing Ar ion beam bombardment achieved a strong bond between GaN and LiNbO3 wafers. The bonded wafer made using the modified SAB method was successfully cut into 1 × 1 mm 2 dies using a dicing saw without interfacial debonding, and the measured tensile strength was estimated to be greater than approximately 26 MPa. These results show the presence of a strong bond that may be sufficient for device applications. In addition, TEM observation clearly indicated that the Fe-containing nanolayer deposited during ion beam bombardment appears to work well as an adhesive and form a strong bond between the negative surface of LiNbO3 and Ga-face of GaN. These results show the potential of this room-temperature bonding method to achieve a future GaN/LiNbO3 hybrid platform that can fully exploit the unique properties of each material.